Total Synthesis and Functional Characterization of Selenoneine. Issue 42 (9th September 2019) - Lim, David; Gründemann, Dirk; Seebeck, Florian P.
Abstract: The N ‐α‐trimethyl 2‐selenohistidine selenoneine is the selenium isolog of the natural antioxidant ergothioneine. Sulfur‐to‐selenium substitutions are known to endow proteins and nucleic acids with special activities. In contrast, secondary metabolites that exploit selenium‐specific chemistry are rare. Selenoneine therefore provides a unique opportunity to study how natural organoselenides interact with cellular processes. In this report we describe the chemical synthesis of selenoneine and other 2‐selenoimidazoles. With synthetic selenoneine at hand we discovered a set of reactivities that distinguish selenoneine from ergothioneine, showing that the two compounds can fill distinct functional niches. Synthetic access to 2‐selenoimidazoles should pave the way to explore the pharmaceutical potential and physiological function of this heretofore inaccessible class of compounds. Abstract : The selenium isolog of the natural antioxidant ergothioneine, selenoneine and other 2‐selenoimidazoles are synthesized. Distinct reactivities are found for selenoneine and ergothioneine, showing that the two compounds can fill distinct functional niches. Synthetic access to 2‐selenoimidazoles paves the way to explore the pharmaceutical potential and physiological function of this heretofore inaccessible class of compounds.